Application of Context-Aware and Collaborative Mobile Learning System Design Model in Interactive E-Book Reader Using Design Thinking Methods - Nalendro, Putu Aji; Wardani, Ratna (Khazanah Informatika, 2020)
E-books as a learning medium have been widely used and utilized to support learning processes. The presence of e-books as digital books can be accepted by users because of the interactive content and display. However, the current format of e-book has not provided a mechanism/platform that accommodates contemporary learning styles on a two-way networked learning basis. E-books are more static in the sense that it has minimal interaction context. E-books have not been able to integrate learners with their learning environment in an interaction construct to support a learning activity. To address this problem, this study recommends a new approach called context-aware and collaborative mobile learning system design model. The method used in implementing the design model is design thinking. Usability testing using the guerrilla usability testing method is carried out to determine the quality of the e-books produced. The results obtained at the stages of empathize and define produced list and learning problems experienced by students when using e-books. The ideate and prototype stages produced e-book prototypes developed based on context-aware and collaborative mobile learning system design model. In the test stage, usability testing of 30 students showed good results. It is said to be good because there are no assignments with a score of one in the rubric usability testing table. So it can be concluded that the design model applied to the prototype e-book is feasible and can be understood by users.